2005
DOI: 10.1093/rheumatology/kei177
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of foot orthoses in the rheumatoid arthritic foot

Abstract: Foot orthoses are commonly prescribed by health professionals as a form of intervention for the symptomatic foot in rheumatoid arthritis. However, there is a limited evidence base to support the use of foot orthoses in this patient group. This article provides a critical review of the use of foot orthoses in the management of rheumatoid arthritic foot pathologies. A search was conducted in the Cochrane Controlled Trials Register (current issue of the Cochrane Library), Physiotherapy evidence database (PEDro), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 23 publications
3
33
0
6
Order By: Relevance
“…Additionally, the lack of completed studies of custom orthoses led to evidence for some outcomes being classified as inconclusive. These results are similar to previous reviews in this area that showed that foot orthoses may be beneficial for some outcomes such as pain (8,9). However, unlike previous reviews, effect sizes were able to be calculated for 3 outcome measures and a level of evidence was assigned for all outcome measures.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Additionally, the lack of completed studies of custom orthoses led to evidence for some outcomes being classified as inconclusive. These results are similar to previous reviews in this area that showed that foot orthoses may be beneficial for some outcomes such as pain (8,9). However, unlike previous reviews, effect sizes were able to be calculated for 3 outcome measures and a level of evidence was assigned for all outcome measures.…”
Section: Discussionsupporting
confidence: 83%
“…Consequently, orthoses are commonly used as an adjunct therapy (7). However, the evidence for the effectiveness of orthoses is lacking, as previously shown in other reviews (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…The suggestion is that by correcting these forces and stabilizing the foot, this may slow or prevent the development of forefoot deformity. Critical reviews have so far not been able to show this to be the case [26,27].…”
Section: Nonoperativementioning
confidence: 99%
“…Previous studies have reported on the clinical effectiveness of foot orthoses in people with established RA, ranging from simple insoles to customised foot orthoses [9][10][11][12]. Clark [13] reported that few studies have undertaken a cost effectiveness analysis to investigate the cost implication of the prescription of foot orthoses for people with established RA, despite the high prevalence of foot involvement and the high direct cost of RA related health care to the UK economy. The issue of the cost effectiveness of providing foot orthoses in the UK National Health Service (NHS) has been raised in chronic musculoskeletal foot conditions [14], as it represents a considerable burden to patients, clinicians and health providers.…”
Section: Introductionmentioning
confidence: 99%